Phenolics composition and antioxidant capacity of guelder rose fruit, flower and bark extracts - Polka, Dominika; Podsędek, Anna (Wydawnictwo Politechniki Łódzkiej, 2019)
Different parts of plants, including fruits, leaves, roots, bark, stem and flower, are a promising source of bioactive compounds, therefore they are intensively studied for biological activity and the possibility of use in functional foods and dietary supplements. The present research compares the phenolic profile and antioxidant capacity of aqueous extracts obtained from bark, flowers and fruits of guelder rose. Antioxidant activity was evaluated against ABTS, hydroxyl and peroxyl free radicals, and as a reducing power by using in vitro test. The total phenolics, flavanols and proanthocyanidins were assessed by spectrophotometric methods, and individual phenolic compounds were also determined using UPLC analysis. Bark water extract proved to be richest in natural antioxidants because it showed the highest antioxidant potential, regardless of the method used. Its very high antioxidant capacity was connected with high phenolic compounds content, especially flavanols and proanthocyanidins. Water extracts of guelder rose fruits and flowers were characterized by the high level of hydroxycinnamic acids, especially chlorogenic acid. It seems that guelder rose bark may be selected as potential source of phytochemicals with high antioxidant potential.
Keywords: Guelder rose; fruits; flowers; bark; phenolic compounds; antioxidant capacity; kalina koralowa; owoce; kwiaty; kora; związki fenolowe; zdolność antyoksydacyjna